Pengaruh Total Harmonic Distortion Terhadap Power Factor Pelanggan Rumah Tangga 900 – 2200 VA Dusun Tujuh Bubung Kepulauan Bangka Belitung - Ummi Khofifah Qodariah Ramadhani; Asmar Asmar; Wahri Sunanda (Institut Teknologi Dirgantara Adisutjipto, 2022)
The high content of harmonics in an electric power system can cause several disturbances to the system, such as increasing power losses in the system, causing various damage to electrical equipment, and causing the use of electrical energy to be ineffective. Harmonics is caused by the operation of non-linear electrical loads. The interacting harmonic currents with the supply system impedance distorts the supplier's output current and voltage which in turn adversely affects the loads connected to the system and the supply itself. This study aims to analyze the quality of THD in Bubung Tujuh Hamlet, Sangku Village. In this study, THD measurements were carried out and analyzed the effect of harmonics on the power factor using a linear regression test. The results of the measurement and analysis of THDV ranged from 1.0% - 6.8%, with the final analysis of THDV still meeting the set standard of 5%. THDI ranged from 2.3% - 66.7% with the final analysis THDI did not meet the standard. THD of the village's electrical system is still at the standard limits set and THD(V) effect on PF.